Analisis Faktor-Faktor yang Mempengaruhi Pertumbuhan Ekonomi di Propinsi Banten - Rosalendro Eddy Nugroho (Universitas Bunda Mulia, 2017)
The amount national economic growth is important to measuring the success of local economic growth. This is because local economic growth is one of indicator to indicate the level of welfare resulting from economic development. Increasing local economic growth also followed by an increasing number unemployed, wage minimum province and national investment company not offset by decreased employment opportunities and foreign investment company. The number of local economic growth in Banten Province was high for the time period 1999-2013. With average of local economic rate is 5.392 percent each year. The high of local economic growth is economic phenomena in Banten Province. Purpose for this paper is to analysis correlation of factors that influence local economic growth rate in Banten Province. Based on the calculation of multiple regression analysis showed that variables related to national investment company a positive and significant at 0.658, at 2,426 wage minimum province is positively related and significant impact on the unemployment rate amounted to 2.749, foreign investment company has a negative and significant at -0.457.Keywords: Unemployment, Employment Opportunitie, Local Economic Growth, National Invesment Company, Foreign Invesment Company.